Faktor - Faktor yang Berhubungan Dengan Perilaku Merokok Remaja Analisis Data Sekunder Di SMAN DKI Jakarta dan SMK Kabupaten Kuningan 2016 - Marwah Berliana Putri; Retno Mardhiati Adiwiryono (Jurnal Pendidikan Kesehatan, 2020)
The number of smokers in Indonesia continues to increase, especially among teenagers. If this continues, it can be confirmed that 10 million people will die from cigarettes per year by 2020, with 70 percent of cases occurring in developing countries such as Indonesia. The purpose of this study is to find out the factors related to adolescent smoking behavior in SMAN DKI Jakarta and SMK Kabupaten Kuningan 2016, taken from secondary data analysis. This research is quantitative research with cross sectional approach. Sampling techniques use saturated sampling techniques with a sample of 410 respondents. This research uses secondary data through the combination of research conducted in SMAN DKI Jakarta and research conducted in SMK Kabupaten Kuningan in 2016. The analysis used is univariate analysis, bivariate in the form of Chi Square test and multivariate analysis with double logistics regression. Univariate results showed respondents to the non smoking group namely 34.6 percent, adolescents namely 95.6 percent, male gender namely 84.6 percent, low knowledge namely 66.6 percent, bad attitudes namely 67.8 percent, easy access to cigarettes namely 84.9 percent, low cigarette advertising exposure namely 71.0 percent. Bivariate results showed variables related to adolescent smoking behavior, namely age and gender. The most dominant multivariate results associated with adolescent smoking behavior are age variables.